Análisis de un dispositivo de monitoreo remoto para el ambiente del data center del GAD Babahoyo - Navarrete Villafuerte, Pedro Julio (2020)
This document related to a case study for the implementation of a system that allows to prevent possible failures and damages within a Data Center in the municipality of Babahoyo Where different perspectives have been determined with different technical points of view that entails or recommends to have be very careful with the training generated and stored by the institution studied. There are many technologies where the Data Center is an information storage center, these must also be protected or have systems that allow early warning of any incident due to temperature change or some other important event that implies risks of damage